Estimates of Oil-Soaked Carcasses of the Magellanic Penguin (Spheniscus magellanicus) on the eastern shore of Península Valdés, Chubut Province, Argentina - Knaus, Ronald M. (El Hornero, 1990)
Este artículo no cuenta con un resumen.